Ultrathin nanoporous membranes for insulator-based dielectrophoresis. (10th April 2018) - Mukaibo 向, Hitomi 坊 仁美; Wang, Tonghui; Perez-Gonzalez, Victor H; Getpreecharsawas, Jirachai; Wurzer, Jack; Lapizco-Encinas, Blanca H; McGrath, James L
Abstract: Insulator-based dielectrophoresis (iDEP) is a simple, scalable mechanism that can be used for directly manipulating particle trajectories in pore-based filtration and separation processes. However, iDEP manipulation of nanoparticles presents unique challenges as the dielectrophoretic force ( F ⃗ D E P ) exerted on the nanoparticles can easily be overshadowed by opposing kinetic forces. In this study, a molecularly thin, SiN-based nanoporous membrane (NPN) is explored as a breakthrough technology that enhances F ⃗ D E P . By numerically assessing the gradient of the electric field square ( ∇ ∣ E ⃗ ∣ 2 ) —a common measure for F ⃗ D E P magnitude—it was found that the unique geometrical features of NPN (pore tapering, sharp pore corner and ultrathin thickness) act in favor of intensifying the overall ∇ ∣ E ⃗ ∣ 2 . A comparative study indicated that ∇ ∣ E ⃗ ∣ 2 generated in NPN are four orders of magnitude larger than track-etched polycarbonate membranes with comparable pore size. The stronger ∇ ∣ E ⃗ ∣ 2 suggests that iDEP can be conducted under lower voltage bias with NPN: reducing joule heating concerns and enabling solutions to have higher ionic strength. Enabling higher ionic strength solutions may also extend the opportunities of iDEP applications under physiologically relevant conditions. This study also highlights the effects of ∇ ∣ E ⃗ ∣ 2 induced by the ion accumulation along charged surfaces (electric-double layer (EDL)). EDL-based ∇ ∣ E ⃗ ∣ 2 exists along the entire charged surface, including locations where geometry-based iDEP is negligible. The high surface-to-volume ratio of NPN offers a unique platform for exploiting such EDL-based DEP systems. The EDL-based ∇ ∣ E ⃗ ∣ 2 was also found to offset the geometry-based ∇ ∣ E ⃗ ∣ 2, but this effect was easily circumvented by reducing the EDL thickness (e.g. increasing the ionic strength from 0.1 to 100 mM). The results from this study imply the potential application of iDEP as a direct, in-operando antifouling mechanism for ultrafiltration technology, and also as an active tuning mechanism to control the cut-off size limit for continuous selectivity of nanomembrane-based separations.